2009
DOI: 10.4028/www.scientific.net/amr.65.89
|View full text |Cite
|
Sign up to set email alerts
|

Residual Strength and Fracture Path for Drilled Epoxy-Glass Composites

Abstract: Aircraft composite structures are mostly joined by mechanical fasteners like bolts, pins or screws. However, the effect of the presence of holes in the remaining strength of the composite structures is still being studied extensively. In this work, epoxy/glass laminates with drilled holes of different sizes were tensile tested and from these results, the residual strength was plotted. Strength vs. hole’s diameter at different fiber orientation was obtained. The fracture path and failure mechanism were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The process implies destruction of fibre continuity with generation of large stress concentration in the material and delamination at the hole entry and exit [2][3][4][5][6][7]. The damage caused can significantly reduce the fatigue strength of the component, thus degrading the long-term performance of composite laminates [8][9]. Previous studies have shown that machining fibre-reinforced polymer (FRP) composites materials differs significantly in many aspects from machining conventional metals and alloys primarily due to the underlying heterogeneity and anisotropy of FRP materials [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The process implies destruction of fibre continuity with generation of large stress concentration in the material and delamination at the hole entry and exit [2][3][4][5][6][7]. The damage caused can significantly reduce the fatigue strength of the component, thus degrading the long-term performance of composite laminates [8][9]. Previous studies have shown that machining fibre-reinforced polymer (FRP) composites materials differs significantly in many aspects from machining conventional metals and alloys primarily due to the underlying heterogeneity and anisotropy of FRP materials [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional drilling (CD) implies large distribution of stress concentration in the materials and also delamination and surface quality degradation (Keonig, et al,1985;Davim and Reis, 2003;Zitoune et al, 2005). This reduces the fatigue strength of components, hence, the long-term performance decreases (Torres et al, 2009;Persson et al, 1997). Stress generated during drilling process can be reduced with the help of UAD because UAD lower level of drilling forces is encountered by workpiece and drill bit.…”
Section: ~ 6 ~mentioning
confidence: 99%
“…Even though the CM process is utilized very frequently in today's manufacturing by selecting suitable cutting parameters and tool geometry, but most of the problems mentioned above remain the major cause of producing surface damage [11]. Such damages can cause significant reduction in tensile and compressive strength and it also decreases stiffness [2], consequently reducing the performance of the entire structure [11] which adds to huge economic burden, as 60% of the rejected components during manufacturing owe to the inferior hole quality [1,11,18,20]. Nonoptimal cutting tool designs, rapid tool wear, and machining conditions can be considered for the above mentioned problems.…”
Section: Introductionmentioning
confidence: 99%